1927 Haw. Sess. Laws 209-17, § 21 - (:unkn) unknown (My University, 1927)
AN ACT Regulating the Sale, Transfer and Possession of Certain Firearms and Ammunitions, and Amending Sections 2136, 2137, 2138, 2139, 2140, 2141, 2142, 2143, 2146 and 2147 of the Revised Laws of Hawaii 1925 (the "Small Arms Act"), § 21: Required the furnishment of a list of all firearms and ammunition in one's possession to the sheriff. Required the sheriff to inspect shops, stores, warehouses, and other business premises of such dealers to verify the accuracy of the reports.
Keywords: REGISTRATION